Time course of tolerance to the performance benefits of caffeine - Lara, B.; Ruiz-Moreno, C.; Salinero, J. J.; Del Coso, J. (PLOS ONE, 2019)
The ergogenic effect of acute caffeine ingestion has been widely investigated; however, scientific information regarding tolerance to the performance benefits of caffeine, when ingested on a day-to-day basis, is scarce. The aim of this investigation was to determine the time course of tolerance to the ergogenic effects of a moderate dose of caffeine. Eleven healthy active participants took part in a cross-over, double-blind, placebo-controlled experiment. In one treatment, they ingested 3 mg/kg/day of caffeine for 20 consecutive days while in another they ingested a placebo for 20 days. Each substance was administered daily in an opaque unidentifiable capsule, and the experimental trials started 45 min after capsule ingestion. Two days before, and three times per week during each 20-day treatment, aerobic peak power was measured with an incremental test to volitional fatigue (25 W/min) and aerobic peak power was measured with an adapted version of the Wingate test (15 s). In comparison to the placebo, the ingestion of caffeine increased peak cycling power in the incremental exercise test by ~4.0 ±1.3% for the first 15 days (P<0.05) but then this ergogenic effect lessened. Caffeine also increased peak cycling power during the Wingate test on days 1, 4, 15, and 18 of ingestion by ~4.9 ±0.9% (P<0.05). In both tests, the magnitude of the ergogenic effect of caffeine vs. placebo was higher on the first day of ingestion and then progressively decreased. These results show a continued ergogenic effect with the daily ingestion of caffeine for 15-18 days; however, the changes in the magnitude of this effect suggest progressive tolerance.